ANALISIS DINAMIKA PERUBAHAN KONSTITUSI PASCA AMANDEMEN UUD 1945 TERHADAP SISTEM DAN PERAN PARTAI POLITIK DI INDONESIA - Rutmawati; Desi Fatma Wati; Octaviani Putri Hutajulu; Dona Sariani; Anggina Ramadani; Hotmariana Simbolon; Kenly Tampubolon; Herliani butarbutar; Rahel Mulyana Marpaung; Dian Novelmi; Imel Syahardila Lanova; Mashuro (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
One of the important milestones in the reform of the Indonesian constitutional system was the constitutional change through the amendments to the 1945 Constitution, which had a significant impact on the political system and the role of political parties. The purpose of this article is to examine how constitutional changes occurred after the amendments to the 1945 Constitution regarding the system and role of political parties in Indonesia, and how these changes impacted the implementation of democracy and elections. This research is a qualitative research using a descriptive approach. This method involves reviewing literature from various journals, scientific articles, and other relevant sources. The study shows that the four amendments to the 1945 Constitution have significantly changed the Indonesian constitutional structure. This includes limiting the authority of the president, increasing the function of the House of Representatives (DPR), creating new institutions such as the Regional Representative Council (DPRD) and the Constitutional Court, and improving the electoral democracy system. With these changes, political parties, which are pillars of democracy, have more room to operate, conduct political education, and participate in a more transparent electoral process. However, in reality, several errors remain, such as transactional politics, political corruption, and manipulation of democratic mechanisms, indicating that constitutional reform has not been fully accompanied by increased political integrity. Therefore, to achieve the ideal goals of constitutional amendment, it is necessary to strengthen the legal system, reform internal political parties, and consistently enforce substantive democracy.